The Security Imperative of Fake News, Hate Speech, and Stereotypical Report in Nigeria - Aruku, Kalita; Mensah, Eyamba Offiong; Ikankang, Fr. Joseph; Igiri, Anthony Bassey (Darul Yasin Al Sys, 2025)
Fake news, hate speech, and stereotypical reporting represent a dangerous weaponization of information, with far-reaching implications for societal trust, cohesion, and security. In an ethnically and religiously pluralistic society like Nigeria, the media plays a pivotal role in peacebuilding and national development. However, this study highlights how, contrary to the expectations of the Social Responsibility Theory of the press, media outlets, particularly social media platforms have at times contributed to deepening divisions and instigating political, religious, and ethnic intolerance. Nigeria's history of recurrent crises over the past six decades, including those that led to predictions of state failure, has often been exacerbated by inflammatory media content. This paper critically examines how the proliferation of fake news and hate speech constitutes a significant security threat, using the Labeling and Social Responsibility Theories as analytical frameworks. Through a case study analysis of past events in Nigeria and globally, the paper underscores the urgent need for a multi-pronged response. Recommendations include implementing robust media literacy campaigns, establishing stronger regulatory mechanisms, and fostering community-driven initiatives. The study emphasizes the amplified influence of social media in spreading divisive narratives, especially among populations increasingly dependent on digital platforms for news. Ultimately, it calls for coordinated efforts among government bodies, civil society organizations, and technology companies to counteract misinformation and cultivate a culture of ethical journalism. Addressing these challenges is critical for safeguarding national unity, fostering peace, and enhancing Nigeria’s security landscape.